Students, How Cognitively Engaged Are You in English Flipped Classrooms?: A Qualitative Study of EFL Learners - Najla AD Budiarto; Elvina Arapah; Fahmi Hidayat; Cayandrawati Sutiono (New Language Dimensions, 2025)
The rapid development of digital technology has encouraged the adoption of innovative instructional models in higher education, including the English Flipped Classroom (EFC). Although widely recognized for promoting autonomy and active learning, empirical evidence on its impact on cognitive engagement among university-level English as a Foreign Language (EFL) learners remains limited and inconsistent. Situated in an undergraduate EFL program at a public university in Banjarmasin City, this qualitative descriptive study explored how first-semester EFL students cognitively engage in an EFC environment using Pohl’s (2020) framework of motivation and cognitive–metacognitive strategy use. Five high-achieving students were purposively selected, and data were collected through semi-structured interviews examining pre-class, in-class, and post-class learning phases. The findings reveal three interrelated patterns of cognitive engagement: sustained motivational engagement through positive task valuation and mastery-oriented goals; strategic learning regulation via independent resource use, peer collaboration, and instructor consultation; and behavioral persistence reflected in consistent time and effort investment across learning phases. While the EFC fostered meaningful cognitive engagement among novice EFL learners, the depth and consistency of engagement varied depending on students’ strategic awareness. These findings suggest that flipped EFL instruction should be supported by explicit scaffolding, such as strategy modeling and guided reflection, to sustain cognitive engagement and optimize learning outcomes.